2020
DOI: 10.1111/1751-2980.12925
|View full text |Cite
|
Sign up to set email alerts
|

Liver damage at admission is an independent prognostic factor for COVID‐19

Abstract: Objective Abnormal liver function is a common form of extra‐pulmonary organ damage in patients with coronavirus disease 2019 (COVID‐19). Patients with severe COVID‐19 have a higher probability and progression of liver injury than those without severe disease. We aimed to evaluate the prognosis of liver injury in patients with COVID‐19. Methods We retrospectively included 502 patients with laboratory‐confirmed SARS‐CoV‐2 infection. Clinical features and survival of patients with and without liver injury were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 19 publications
(26 reference statements)
3
31
0
5
Order By: Relevance
“…( 14 ) This trivial difference makes AST alone less ideal to predict COVID‐19 outcomes. In contrast, FIB‐4 includes AST and age as numerators, which are positively correlated to liver fibrosis ( 6,10,15 ) ; it also reflects the AST dominant pattern in COVID‐19 reported by earlier studies, ( 4,16 ) as well as age, which has been shown since early in this pandemic to be one of the strongest indicators of adverse outcomes, including death. ( 2 ) These features make the FIB‐4 score a better predictor compared with any of its components alone.…”
Section: Discussionmentioning
confidence: 93%
“…( 14 ) This trivial difference makes AST alone less ideal to predict COVID‐19 outcomes. In contrast, FIB‐4 includes AST and age as numerators, which are positively correlated to liver fibrosis ( 6,10,15 ) ; it also reflects the AST dominant pattern in COVID‐19 reported by earlier studies, ( 4,16 ) as well as age, which has been shown since early in this pandemic to be one of the strongest indicators of adverse outcomes, including death. ( 2 ) These features make the FIB‐4 score a better predictor compared with any of its components alone.…”
Section: Discussionmentioning
confidence: 93%
“…Other important pathological features observed include hepatic necrosis and mild portal and lobular lymphocytic infiltration, 48,53,54 with no concrete evidence of liver injury 18 . Liver biopsies taken from 48 fatal cases of SARS‐CoV‐2 infection revealed major vascular alterations with minimal hepatic inflammation 55 . Some cases also exhibited fibrosis of the portal tract 55 .…”
Section: Histopathological Alterations In the Livermentioning
confidence: 99%
“…Liver biopsies taken from 48 fatal cases of SARS‐CoV‐2 infection revealed major vascular alterations with minimal hepatic inflammation 55 . Some cases also exhibited fibrosis of the portal tract 55 . It is likely that the liver does not undergo significant inflammatory damage during SARS‐CoV‐2 infection, and the hepato‐vascular alterations observed are a secondary response to systemic changes induced by SARS‐CoV‐2.…”
Section: Histopathological Alterations In the Livermentioning
confidence: 99%
See 1 more Smart Citation
“…Cai et al [44] showed that 76.3% of COVID-19 patients present with liver injury and 21.5% show liver damage in a study with 417 patients. A study by Chen et al [45] involving 502 COV­ID-19 patients revealed that liver abnormalities represent an indicator of severe disease, including higher rates of systemic inflammatory response syndrome and death.…”
Section: Covid-19 and Liver Damagementioning
confidence: 99%